The shadow banking behaviour in internet of things: evidence from economy operation mode in China - Yang, Ling; Shen, Chung-Hua (Technological and Economic Development of Economy, 2024)
With the acceleration of world economic integration and enterprise management globalization, the advent of Internet of things based on Internet and information technology has become inevitable. The Internet of things also brings about a cascading effect between firms’ shadow banking behaviour and bank connections. This study investigates the relationship between firms’ shadow banking behaviour and bank connections by analysing a sample of Chinese listed firms in Internet of things industry. The results show that bank connections eliminate information asymmetry between banks and firms, bank connections are positively related to firms’ long-term debt, and as long-term debt increases, firms’ shadow banking behaviour also increases. Furthermore, this finding shows very strong robustness, the empirical analysis provides sufficient evidence that firms’ shadow banking behaviour increased with bank connections in Internet of things industry. In addition, the evidence also shows that the tendency of shadow banking behaviour is more pronounced in non-state-owned enterprises (NSOEs) than state-owned enterprises (SOEs) by sub-sample sensitivity analysis.First published online 17 March 2022